Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2011
DOI: 10.1074/jbc.m111.265348
|View full text |Cite
|
Sign up to set email alerts
|

Deletion of Betaine-Homocysteine S-Methyltransferase in Mice Perturbs Choline and 1-Carbon Metabolism, Resulting in Fatty Liver and Hepatocellular Carcinomas

Abstract: Betaine-homocysteine S-methyltransferase (BHMT) uses betaine to catalyze the conversion of homocysteine (Hcy) to methionine. There are common genetic polymorphisms in the BHMT gene in humans that can alter its enzymatic activity. We generated the first Bhmt Histopathological analysis revealed that Bhmt ؊/؊ mice developed hepatocellular carcinoma or carcinoma precursors. These results indicate that BHMT has an important role in Hcy, choline, and one-carbon homeostasis. A lack of Bhmt also affects susceptibility… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

9
184
2
3

Year Published

2012
2012
2022
2022

Publication Types

Select...
5
2

Relationship

1
6

Authors

Journals

citations
Cited by 182 publications
(198 citation statements)
references
References 53 publications
9
184
2
3
Order By: Relevance
“…We observed that Bhmt-deficient (Bhmt Ϫ/Ϫ ) mice had a lower body weight from 5 to 9 weeks of age compared with wild type littermates (2). Magnetic resonance image (MRI) analysis and dissection of adipose fat depots revealed that the reduced * This work was supported, in whole or in part, by National Institutes of body weight observed in Bhmt Ϫ/Ϫ mice was due to reduced fat depots.…”
Section: Betaine-homocysteine S-methyltransferase (Bhmt)mentioning
confidence: 92%
See 3 more Smart Citations
“…We observed that Bhmt-deficient (Bhmt Ϫ/Ϫ ) mice had a lower body weight from 5 to 9 weeks of age compared with wild type littermates (2). Magnetic resonance image (MRI) analysis and dissection of adipose fat depots revealed that the reduced * This work was supported, in whole or in part, by National Institutes of body weight observed in Bhmt Ϫ/Ϫ mice was due to reduced fat depots.…”
Section: Betaine-homocysteine S-methyltransferase (Bhmt)mentioning
confidence: 92%
“…Adipocytes-We previously reported that Bhmt Ϫ/Ϫ mice gained less body weight between 5 and 9 weeks of age than did their wild type littermates (p Ͻ 0.05) (2). To determine whether the reduced weight gain of Bhmt Ϫ/Ϫ mice was associated with reduced fat or lean mass, we measured body composition of these mice using MRI scan analysis.…”
Section: Bhmt Deficiency Resulted In Reduced Fat Mass and Smallermentioning
confidence: 99%
See 2 more Smart Citations
“…SAHH dysfunction is linked to numerous pathologies such as neurological and vascular disorders, myopathy, fatty liver, cancer, renal insufficiency, and diabetic nephropathy (5)(6)(7)(8)(9)(10)(11)(12)(13). Deletion of SAHH in mice is embryonically lethal (14).…”
mentioning
confidence: 99%